Penerapan Manajemen Balance Scorecard (BSC): Studi Kasus di MIS Miftahul Ulum Kec. Serpong Utara Kota Tangerang Selatan - Jamilah Muryati; Aris Munandar; Naufal Hilmizen; Elis Lisyawati; Rokhayati Rosa; Ida Tejawiyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implementation of Balanced Scorecard (BSC) management at MIS Miftahul Ulum, Serpong Utara District, South Tangerang City is still facing some obstacles. The lack of understanding and accurate data, structured systems, resources, and accountability culture are the main barriers. This has resulted in the suboptimal achievement of strategic goals, such as learning, internal process, customer, and financial indicators that are not yet maximized. The purpose of this study is to determine the extent to which the implementation of Balanced Scorecard (BSC) management at MIS Miftahul Ulum, reviewed from four perspectives, namely: financial, customer, internal process, and learning and growth. This research is qualitative, with data collection methods including interviews, observations, and documentation. Data validity is ensured through triangulation, and data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. The research shows that the quality of education at MIS Miftahul Ulum, Serpong Utara District, South Tangerang City has improved compared to previously. However, some adjustments need to be made in the implementation of Balanced Scorecard (BSC). Conclusion: MIS Miftahul Ulum focuses on diversifying funding sources, increasing the efficiency of fund management, and increasing income from voluntary donations. Customer satisfaction and making MIS Miftahul Ulum the main school of choice for students and parents. Progress in its internal processes by implementing a quality curriculum, an effective teaching and learning process, and timely completion of teaching and learning tasks, and a quality curriculum provides a strong foundation for students to learn and grow. Effectiveness of the teaching and learning process: An effective teaching and learning process allows students to reach their full learning potential. Timely completion of teaching and learning tasks: Timely completion of teaching and learning tasks ensures that students have enough time to learn and understand the subject matter.